MEKANISME PENGELOLAAN ROYALTI DARI PEMUTARAN LAGU DI KAFE (STUDI PENELITIAN KOPI NAKO CABANG GALAXY DAN C CODE COFFEE TOMANG): Royalty Management Mechanism from Song Play in Cafes (Research Study of Coffee Nako Galaxy Branch and C Code Coffee Tomang) - Muhammad Faris Mahardhika; Rakhmita Desmayanti (AMICUS CURIAE, 2025)
Every copyrighted work has economic rights for its creator, in the form of royalties. That way the creator has the right to get economic benefits from announcing or disseminating a work or giving permission to other parties to use his work. The government based on Law Number 28 of 2014 (UUHC) created the National Collective Management Agency (LMKN) which is responsible for the management of song or music royalties. LMKN withdraws royalties to commercial users, one of which is a cafe that plays songs, besides that LMKN must also distribute royalties to songwriters through the Collective Management Institute (LMK). Related to royalty management is regulated in Government Number 56 of 2021 concerning Royalty Management for Copyright of Songs and/or Music. The subject matter is how the mechanism for withdrawing royalties as the economic rights of creators from playing songs in cafes and how the mechanism for distributing royalties to songwriters. The type of research used is normative with secondary data, which is supported by primary data. The nature of the research is descriptive and deductive inference. Based on the results of the research, it is concluded that LMKN as an institution responsible for the management of song royalties has carried out the management properly in accordance with PP 56/21, but cafes as commercial users still lack awareness to pay royalties.